The Greek Crisis in Perspective: Origins, Effects and Ways-out - Christodoulakis, Nicos (Études helléniques / Hellenic Studies, 2014)
In 2011 the Euro faced its toughest challenge since its introduction as several of the participating Member States faced unprecedented financial problems. Greece was the most severe case requiring intervention from the EU and IMF to stabilize its economy and repay debt obligations. This article explains the debt process in Greece from the 1980s to date, and describes its main causes and episodes. It also assesses the IMF-EU Memorandum and argues that the collapse of growth inhibits the prospects of debt stabilization. An alternative scenario is discussed that shows that stabilization can become more effective and is realistic if the recession is tackled first and reforms follow on a steadier path.